Ovarian Reserve and Ultrasound Doppler of Stromal Blood Flow-A Prospective Longitudinal Study - Chakrabarti, Sudakshina; Madhu, Shravya; ShahaniKaisery M, Shifana; Sharma, Nidhi (International Journal of Psychosocial Rehabilitation, 2020)
The ovarian stromal vascularity is important to provide the necessary gonadotrphin to the developing follicles both in natural and stimulated cycles for their maturation and subsequent recruitment. The development of follicle is a coordinated and complicated process in which there are involvement of multiple paracrine and endocrine factors too. In this study Colour Doppler Ultrasound is used to study the ovarian stromal blood flow. Aims and Objectives: The primary objective is to determine the predictive value of Color Flow Doppler Indices in ovarian stroma in predicting ovarian reserve, oocyte quality and maturity in controlled ovarian stimulation in GnRh antagonist step down protocol. This is a prospective experimental study comprising 30 patients.Ultrasound 2 D colour Doppler was done on Day 2 –Day 3 of menstrual cycle. Mean resistivity index and mean pulsatility index of right and left ovaries were recorded. All 30 patients underwent controlled ovarian stimulation with step down dosage of gonadotropins .GnRH (Gonadotropin Releasing Hormone) antagonist from day 5 of cycle (fixed multiple dose antagonist protocol) was used to prevent premature LH surge. Ovarian stromal Resistivity Index (RI) and Pulsatality Index (PI) can be used to predict low ovarian reserve. 2D Colour Doppler flow mode which is easily available to measure the ovarian stromal blood flow indices (RI, PI) showed prominent correlation with the of mature M2 oocytes retrieved in patients undergoing controlled ovarian stimulation. Conclusion: 2D colour Doppler ultrasound is a safe and noninvasive and easily available modality for prediction of IVF outcome and also for determining the ovarian reserve in infertile women It is also a reliable predictor to counsel couples seeking infertility treatment.